An Analysis of Loan Loss Provisioning behaviour- An empirical research of Hong Kong and Taiwan Commercial Banks - WEI, Chunyu (2018)
This study examines loan loss provisions behaviour in Hong Kong and Taiwan commercial banks between the years 2011-2017, and used a panel database to observe banks, for the sample is 16 Hong Kong banks and 22 Taiwan banks. In addition, this study uses the generalized method of moments (GMM) estimator to examine a dynamics loan loss provisions model. Further, we will test the correlation and significance between loan loss provisions and three hypotheses, which are contained: income smoothing, capital management and business cycle hypothesis. Through this method, we can analysis clearly the loan loss provisions behaviour in Hong Kong and Taiwan banks. This study aims to identify the internal and external determinants of loan loss provisions of Hong Kong and Taiwan banks and analysis the hypotheses whether affect the bank's loan loss provisions. We find results show that income smoothing hypothesis is an important determinant of loan loss provisions in Hong Kong and Taiwan banks. Also, the capital management hypothesis and counter-cyclical effect would impact on loan loss provisions in Taiwan Banks.